About Chemical Strategies to Fabricate Cell‐Instructive Biointerfaces with Static and Dynamic Complexity. Issue 14 (2nd May 2018) - Koçer, Gülistan; Jonkheijm, Pascal
Abstract: Properly functioning cell‐instructive biointerfaces are critical for healthy integration of biomedical devices in the body and serve as decisive tools for the advancement of our understanding of fundamental cell biological phenomena. Studies are reviewed that use covalent chemistries to fabricate cell‐instructive biointerfaces. These types of biointerfaces typically result in a static presentation of predefined cell‐instructive cues. Chemically defined, but dynamic cell‐instructive biointerfaces introduce spatiotemporal control over cell‐instructive cues and present another type of biointerface, which promises a more biomimetic way to guide cell behavior. Therefore, strategies that offer control over the lateral sorting of ligands, the availability and molecular structure of bioactive ligands, and strategies that offer the ability to induce physical, chemical and mechanical changes in situ are reviewed. Specific attention is paid to state‐of‐the‐art studies on dynamic, cell‐instructive 3D materials. Future work is expected to further deepen our understanding of molecular and cellular biological processes investigating cell‐type specific responses and the translational steps toward targeted in vivo applications. Abstract : Cell‐instructive biointerfaces with static properties have tremendously increased the understanding on processes governing cell–material interactions while dynamic cell‐instructive biointerfaces have opened up the way to spatiotemporally and externally control cell behavior in a more biomimetic context. The achievements fuel the development of new smart biomaterials to guide desired cell and tissue response for regenerative medicine applications.